Assessing Responsiveness of Primary Healthcare Facilities in Rawalpindi: A Cross-Sectional Study - Bukhari, Syed Imran; Mahmood, Humaira; Imtiaz, Nimbal; Shahid, Muhammad Salman; Jogezai, Alamgir; Rehman, Amber (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess responsiveness at First Level Healthcare Facilities at Rawalpindi by using an adapted WHO World Health Survey tool.Study Design: Cross-sectional study.Place and Duration of Study: Three first level care facilities of Nationally Administered Healthcare Organization at Rawalpindi, Pakistan from Jan 2024 to 2024.Methodology: Four Hundred participants were included in the study through nonprobability consecutive sampling following the inclusion criteria after informed consent. The data was collected by one to one interviews held on with outdoor patients presenting in these facilities using WHO World Health Survey tool. Data analysis was done using Statistical Package of Social Sciences (SPSS) software version 21.Results:  Out of 400 participants, 104(26%) perceived that responsiveness was poor in the First Level Care Facilities at Rawalpindi whereas majority 278(69.5%) of the patients found the responsiveness as satisfactory. A mere 18(4.5%) considered responsiveness as good. Out of the essential elements of the responsiveness, Prompt attention was considered the most important by 123(30.8%) participant and 74(18.5%) respondents rated communication as an equally important part of the responsiveness in health care system. The least important domain as considered by the respondents were the choice of provider and social support by 10(2.5%) and 4(1%) respondents respectively.Conclusion: Following the results of the study conducted, the domains of responsiveness still need improvement to enhance patient satisfaction and is directly associated with the domains of responsiveness. However, it is the need of an hour to standardize ..